2019
DOI: 10.1158/2159-8290.cd-18-0469
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A Kinase Inhibition Is Synthetic Lethal with Loss of the RB1 Tumor Suppressor Gene

Abstract: Loss-of-function mutations in the retinoblastoma gene RB1 are common in several treatment-refractory cancers such as small-cell lung cancer and triplenegative breast cancer. To identify drugs synthetic lethal with RB1 mutation (RB1 mut), we tested 36 cell-cycle inhibitors using a cancer cell panel profi ling approach optimized to discern cytotoxic from cytostatic effects. Inhibitors of the Aurora kinases AURKA and AURKB showed the strongest RB1 association in this assay. LY3295668, an AURKA inhibitor with over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 52 publications
9
135
0
Order By: Relevance
“…The methods for generating resistant cell lines were described previously. 34 Briefly, MDA-MB-361, T47D and MCF-7 ER+ breast cancer cell lines were used to derive variants with acquired resistance to abemaciclib or palbociclib. T47D (HTB-133), MCF-7 (HTB-22) and MDA-MB-361 (HTB-27) were purchased from The American Type Culture Collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…The methods for generating resistant cell lines were described previously. 34 Briefly, MDA-MB-361, T47D and MCF-7 ER+ breast cancer cell lines were used to derive variants with acquired resistance to abemaciclib or palbociclib. T47D (HTB-133), MCF-7 (HTB-22) and MDA-MB-361 (HTB-27) were purchased from The American Type Culture Collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies implicate Aurora kinases (AURKA or AURKB) that regulate mitotic spindle assembly and chromosome segregation as alternative therapeutic targets. Independent CRISPR/Cas9 (Oser et al, 2019) and drug screening assays (Gong et al, 2019) using Rb1-deficient classical SCLC cell lines simultaneously identified a unique dependence upon AURK for survival. In these studies, AURK inhibitors potently suppressed the growth of Rb1-negative SCLC cells but had no effect on Rb1-positive lung cancer cells (including the EGFR mutant cell lines H1975 and PC9).…”
Section: Targeting Unique Cell Cycle Vulnerabilities Created By Rb1 Lossmentioning
confidence: 99%
“…In addition, cell death may not necessarily occur through inhibition of a canonical Aurora B kinase signaling. Recently, a noncanonical dependency for Aurora B kinase function was described for SCLC cell lines in which the RB tumor suppressor function is lost (24). In these cells, Aurora B kinase inhibition induced rapid cell death due to a dependence on an alternate checkpoint function.…”
Section: Discussionmentioning
confidence: 99%